What does it cost Medicare to diagnose and treat men with localized prostate cancer in the first year?. Issue 3 (16th March 2017) - Mervin, Merehau C; Lowe, Anthony; Gardiner, Robert A; Smith, David P; Aitken, Joanne; Chambers, Suzanne K; Gordon, Louisa G
Abstract: Objective: To estimate costs on the Medicare Benefits Schedule (MBS) and the Pharmaceutical Benefits Scheme (PBS) attributable to the diagnosis and treatment of prostate cancer. Methods: We used data from a cohort study of 1064 men with localized prostate cancer recruited between 2005 and 2007 by 24 urologists across 10 sites in Queensland, Australia (ProsCan). We estimated the MBS and PBS costs attributable to prostate cancer from the date of initial appointment to 12 months after diagnosis in 2013 Australian dollars using a comparison group without prostate cancer. We used generalized linear modeling to identify key determinants of higher treatment‐related costs. Results: From the date of initial appointment to 12 months postdiagnosis, the average MBS costs attributable to prostate cancer were $9, 357 (SD $191) per patient. These MBS costs were most sensitive to having private health insurance and the type of primary treatment received. The PBS costs were higher in the control group than in the ProsCan group ($5, 641 vs $1, 924). Conclusions: The costs of treating and managing prostate cancer are high and these result in a substantial financial burden for the Australian MBS. Costs attributable to prostate cancer appear to vary widely based on initial treatment and these are likely to increase with the introduction of more expensive services and pharmaceuticals. There is a pressing need for better prognostic tools to distinguish between indolent and aggressive prostate tumors to reduce potential over treatment and help ease the burden of prostate cancer.